Toward scalable management of multiple service levels in IP networks - Lima, Solange (2007)
This paper analyzes and discusses the role of a distributed and simple admission control (AC) model in achieving scalable management of multiple network service levels. The model design, covering explicit and implicit AC, exhibits relevant properties which allow managing QoS and SLSs in multiservice IP networks in a flexible and scalable manner. These properties stem from the way service-dependent AC and on-line service performance monitoring are proposed and articulated in the model's architecture and operation. The scalability debate, carried out at these two levels, highlights key steps toward performing self-adaptive service-oriented AC and low overhead multiservice monitoring. The performance evaluation results, illustrating the role and relevance of the defined AC rules, show that QoS and SLSs requirements can be efficiently satisfied or bounded, proving that the simplicity, flexibility and self-adaptability of the model can be explored to manage multiple service guarantees successfully.